ANALISIS FRAMING BERITA PENGESAHAN RUU KUHP PADA MEDIA ONLINE CNBC INDONESIA.COM - Sitompul, Nia Hafiza; Zuhriah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This research was motivated by the passage of the Criminal Code Bill which caused many pros and cons among the public because of the existence of articles that were considered controversial and became a topic that was widely discussed, especially until the massive demonstration in 2019 that rejected changes to the Criminal Code Bill. The object of this study is two news about the Criminal Code Bill published on the same day after its ratification by the House of Representatives of the Republic of Indonesia on December 6, 2022. The author examines using descriptive qualitative methods supported by a constructive approach by analyzing data medel Zhongdan Pan and Gerald M. Kosicki. The two published news can be interpreted as a forum that clarifies the newly inaugurated Criminal Code Bill in order to keep the atmosphere conducive by presenting explanations and forms of criticism to the government over the new bill. The result is that the two stories studied in the same news portal have similarities in terms of news leads, but the topics raised are very different, the first news highlights endorsements and flashbacks of rejection. While the second news highlights the aspect of the problem after the passage of the Criminal Code Bill regarding the adultery article.